Association of Glaucoma with Hypertension and Diabetes: A Single-Center Study - Rahat Anwer Choudhury; KhondokarAnowar Hossain; Khalifa Mahmud Walid; Moutusi Pramanik (Asian Journal of Medical Research, 2025)
Background: Glaucoma is a chronic and progressive optic neuropathy, a common eye disease that causes structural and functional damage to the optic nerve, which connects the eye to the brain. It remains one of the leading causes of irreversible blindness worldwide, including in Bangladesh. Characterized by optic nerve damage and corresponding visual field loss, glaucoma often progresses silently until significant vision has been lost, making early detection critical for effective management. Among the known risk factors, increasing attention has been focused on systemic diseases such as diabetes mellitus and hypertension—both of which are prevalent and growing public health challenges in Bangladesh. Diabetes mellitus, a metabolic disorder with rising incidence in the Bangladeshi population, is associated with various ocular complications. Recent evidence suggests that diabetic individuals may be at higher risk of developing glaucoma, particularly primary open-angle glaucoma (POAG), due to microvascular damage, impaired auto regulation of ocular blood flow, and neurodegenerative changes in the optic nerve. Hypertension, similarly widespread in the country, has also been implicated in the pathophysiology of glaucoma. It is hypothesized that chronic elevated blood pressure may contribute to increased intraocular pressure (IOP) and reduced optic nerve perfusion. Objectives: The aim of this study is to assess the association of glaucoma in patients with diabetes and hypertension. Methods: This is an observational study. The present study was conducted among 80 diagnosed Glaucoma patients also suffering either for diabetes or hypertension or both attending the ophthalmology outpatient department of BNSB Zahurul Haque Eye Hospital for routine glaucoma follow-up for the duration of the period from January 2022 to December 2023 to assess the association of severity of glaucoma in patients with diabetes and hypertension. Data was entered in MS Excel and Statistical analysis was done using the SPSS-24 version. Results: According to the age of 80 Patients aged <20 to ≥50 years. Here according to Age distribution, 9(11.25%) were 20-29, 13(16.25%) were 30-39, 17(21.87%) were 40-49, and 41(50.62%) were ≥50. The total study population was 80 patients, according to gender 42(48.13%) were Male, 38(51.87%) were Female. The Glaucoma patients with diabetes, hypertension and both were 53%, 35% and 12% respectively. Severity of VFD in Patients with Diabetes and Hypertension according to severe, moderate and mild was 7.3%, 4.5% and 0.8% respectively. The p-value was 0.0046. Conclusions: Glaucoma patients with HTN, DM, or both were found to have more severe. Patients with these risk factors could represent “high-risk patients” with glaucoma. Patients with HTN and DM, or both may require evaluations on a more frequent basis to access the progression/severity of Glaucoma.